Proses Kreatif Komponis Kontemporer Slamet Abdul Sjukur dalam Berkarya Seni - Elizabeth Suryani Ongko; Warih Handayaningrum; Eko W. Rahayu (Universitas Gadjah Mada, 2022)
Artwork is part of a culture that is created because of a process related to constructive creativity. This process is often referred as the creative process. The creative process can be viewed from related aspects, influencing elements, or the stages in it. The creative process that will be discussed by researcher is the creative process of a music artists who want to create something new and unique, often referred to as new music or contemporary music. The purpose of this study is to see how the stages of the creative process of contemporer composer Slamet Abdul Sjukur in creating the artwork. The method of this research is a qualitative research with literature studies, interviews and also observations of Slamet's artworks as the research subjects. Slamet is a composer who emphasizes the simple concept of producing something great, a concept known as the minimax concept. From this study, it was found that Slamet Abdul Sjukur is a contemporary composer who involves all stages of the creative process in creating artwork. However, the details of the stages of ideas and the implementation of Slamet's creative process on one artwork are very different from one another. This then makes each of Slamet's artworks have their own uniqueness.